Development of Control System for Keropok Keping Drying Machine - Muhammad Naim, Leman; Shahrol, Mohamaddan; Mohamad Syazwan Zafwan, Mohamad Suffian; Abang Mohamad Aizuddin, Abang Mohd Mohtar (EDP Sciences, 2016)
This research is focused on the development of a control system for the keropok keping drying machine by using programmable logic controller (PLC) as the controller. The control panel and human machine interface (HMI) were developed for the machine. Experimental study was conducted to validate the HMI speed data by the control panel speed display. The evaluation of the duty cycle (%) and current flow (amp) effect to the motor and fan speed were also conducted. The results showed that around 1 - 30 % and 1 - 3 % differences of the speed readings were recorded by the HMI for the motor and fan respectively. The percentage difference needs to be controlled as small as possible to ensure the HMI speed readings are more accurate. The linearity of the current flow curve to all duty cycle can be observed. The flow (amp) increases when the speed of dryer motor and fan increases. The development of the control system is expected to improve the operation of the keropok keping drying machine.